Medical informatics in obstetrics and gynecology - Parry, David; Parry, Emma, 1968- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
"This book describes a number of areas within women's health informatics, incorporating a technology perspective"--Provided by publisher.